Nurses and COVID-19: Ethical Considerations in Pandemic Care - Ulrich, Connie M.; Grady, Christine; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book addresses the many ethical issues and extraordinary risks that nurses and others are facing during the COVID-19 pandemic, which creates physical, emotional, and economic burdens, affecting nurses' overall health and well-being. Nurses are essential front-line clinicians across all health care settings and in every nation. The COVID-19 pandemic caused by the novel SARs-CoV-2 virus has affected children, adults, and communities within and across all societies. Nurses, too, have contracted the virus and died from the disease. They have also seen their colleagues, family members, and friends hospitalized or in intensive care units struggling to survive. Nursing$1 (Bs professionalism and disciplinary resolve to care for patients and families amidst confusion, misinformation, and shifting guidelines has been called (3z(Bheroic(3y (Bby the public. How much risk should nurses be expected to accept during a pandemic? How do nurses help patients and families find comfort and dignity at the end-of-life? How do we help nurses who are suffering from moral distress and mental health concerns from what they have seen, been asked to do, or are unable to provide? And, how does society move forward from a pandemic that has challenged our basic ethical principles of justice and what is (3z(Bfair, good and right(3y (Bin caring for those who need care, including the most vulnerable and nurses themselves? This book addresses these and other ethical concerns that nurses are facing in their day-to-day clinical practice; experiences shared with patients, families, and colleagues. Although this book was written while the pandemic was still raging across the United States and globally, the events needed to be told as they were unfolding. This book helps us to learn from both the successes and failures that are affecting so many across the globe, including those on whom the public relies on to provide quality, compassionate, and expert care when they are sick: nurses. .s
Introduction -- Understanding Acceptable Risks in Healthcare [Occupational risks/limits/PPE/obligations] -- Finding Compassion: Helping Patients Die and Sometimes Alone -- Preparing to Make Difficult Choices: Triage Decision and Crisis Standards of Care -- The Emotional and Moral Remnants of COVID-19: Burnout, Moral Distress, and Mental Health Concerns -- Unintended Consequences: Lack of Essential and Nonessential Patient Care, Furloughs of HCP, and Institutional Financial Losses -- Lingering and Glaring Health Disparities amidst COVID-19 -- School nurses/pediatric concerns. (3z(BSchool Health -- Chapter 9. Global Health Ethics: Nursing Voices from China and Brazil.-Moving Forward: What Have We Learned? Where do we go from here? [Conclusion] (Opportunities to move forward). .s
Keywords: Nursing ethics; Epidemiology; Bioethics; Nursing Ethics; Epidemiology; Bioethics; Ethics, Nursing; COVID-19